1984
DOI: 10.1002/pssa.2210810230
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Effects in ODMR Spectra of ZnSe:Mn)

Abstract: Manganese and donor‐acceptor luminescence in ZnSe is investigated by optically detected magnetic resonance (Odmr). Resonances due to the Mn2+ ground state are observed not only in the 4T1 → 6A1 emission band of Mn2+ but in two donor‐acceptor recombination bands. Possible mechanisms for the transfer of the ground state resonance to the excited states are discussed. Cross relaxation is the most probable effect. Moreover, spin memory manifests itself in the influence of the excitation polarization on ODMR signals. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The observation of the Mn2+ ground state resonance in both emission bands proves that there is an energy transfer between the different emitting centres, as previously discussed by Kluge et al [4]. Because of the new ODMR-PLE measurements, contrary to [4], we are able to distinguish two different transfer mechanisms.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The observation of the Mn2+ ground state resonance in both emission bands proves that there is an energy transfer between the different emitting centres, as previously discussed by Kluge et al [4]. Because of the new ODMR-PLE measurements, contrary to [4], we are able to distinguish two different transfer mechanisms.…”
Section: Discussionsupporting
confidence: 74%
“…ODMR spectra of Zn,_.Mn,Se have already been published by Kluge et al [4] and Abraham et al [5], who observed the Mn2+ ground state resonance in all emission bands occurring. They discussed this result in terms of energy transfer mechanisms, but due to lack of information, they were not able to give precise information about the way how the Mn2 + ground state resonance influences the observed emission bands.…”
Section: Introductionmentioning
confidence: 88%
“…Our ODMR investigations confirm thus relaxation of spin selection rules of the Mn 2+ intra-shell PL and allow to relate the effect to spin cross The cross-relaxation mechanism of the ODMR detection was also discussed in Refs. [6,7]. We can thus conclude that for close associates of Mn ions spin cross-relaxation processes are efficient and the PL decay time is shorter than that observed for isolated Mn ions.…”
mentioning
confidence: 78%
“…The rel evant m echani sm s were pro p osed by Zi nk and co-workers [6] a nd by Kl uge and Donecker [7]. Zi nk et al .…”
Section: Exp Er I M Ental R Esu L T S An D Discussionmentioning
confidence: 99%
“…[6] pro p osed a cross-rel axati on pro cess of a spin Ûip b etween exci ted D AP and Mn i ons or b etween a pai r of two adj acent Mn i ons, of whi ch one i s in the gro und sta te and one i s i n the exci ted state. In turn, Kl ug e and D onecker [7] pro p osed spin-dep endent tra nsfer. In the l atter pro cess D APs and Mn i ons tra nsfer thei r excita ti on energy and the pro cess depends on thei r spin ori enta ti on.…”
Section: Exp Er I M Ental R Esu L T S An D Discussionmentioning
confidence: 99%